AB0947 Characteristics of a transition clinic for young people with rheumatic diseases. (15th June 2017) - Serrano-Benavente, B; Lόpez-Robledillo, JC; Clemente, D; Monteagudo, I; Nieto-González, JC
Abstract : Background: Paediatric rheumatologic diseases can still be active in the adulthood. Transitional care units are very important for the transition from paediatric to adult health care system. Objectives: To describe the demographic characteristics, paediatric rheumatologic diseases distribution and active treatments in a Rheumatologic Transitional Care Unit (RTCU). Methods: We included all new patients who attended the RTCU of a tertiary level hospital from 1st September 2015 until 31st December 2016. These patients were remitted from the paediatric rheumatology unit of two tertiary level hospitals. We retrospectively analyzed their demographic, laboratory and treatment characteristics. The connective tissue diseases (CTD) group included systemic lupus erythematosus, Behçet disease, dermatomyositis and scleroderma. Patients were considered active according to the physician opinion. Results: We attended 81 new patients. 59 were female (72.8%) and the median age (range) was 19 years (18.1–20.7). 65.43% were diagnosed with Juvenile Idiopathic Arthritis (JIA) and 12.35% with CTD. Table 1 shows the main baseline characteristics of the patients. In the first visit at the unit, half of the patients did not have any systemic treatment (41 patients [50.62%]). From the remaining 40 patients with systemic treatment, 16 patients (40%) were under biologic treatment, mostly anti-TNFα. In any of the two first appointments, 20 patients (24.7%) were active, most of them from the JIA group. Seven (35%) of these patients increased or changed the treatment, 6 of them initiating a biologic treatment. Conclusions: Our RTCU received mostly JIA patients. Median age at arriving was slightly higher than expected. A fourth of patients were active in the transition moment. All this data highlights the need of an strict control of these patients in the transitional period. References: Foster HE. Ann Rheum Dis 2016;0:1–8. Calvo I. Rheumatol Int (2015) 35:1615–1624. Disclosure of Interest: None declared